Improving Structure Mastery By Using Recount TextUnderstanding For The Second Year Students Of SMP Negeri 3 Kartasura In 2010/2011 - PRASETYANINGRUM, YULINDA (2012)
The objectives of the study are as follows: 1) to know whether or not the recount text understanding improve students' structure mastery, 2) to describe the implementation of teaching structure using recount text understanding, 3) to identify the problems of teaching structure using recount text, and 4) to describe the advantages and diadvantages of teaching structure using recount text for the second year students of SMP N 3 Kartasura in 2010/2011. It is Classroom Action Research (CAR) conducted for the second year students of SMP N 3 Kartasura in 2010/2011. The research consists of three cycles preceded by pre-test and ended by post-test. It is implemented through planning, implementing, observing, and reflecting phases. The results of the study show that: 1) The recount text understanding can improve the students' structure mastery. It is proved by the students' average score which increased after having some steps conducted by the teacher. 2) The use of recount text understanding in improving students' structure mastery is effective. The effectiveness can be proved by the increase of students' score throughout the cycle, 3) The problems occurred in the implementation of teaching structure using recount text came from both the student and the teacher. The students were having troubles because they had a lack of vocabulary. They could not differentiate the verb over noun, adverb, and other categories. While the teacher had a problem with the lack of time in preparing the media. Sometime, the teacher should give many recount texts with topics that the students were interested in. Then the students asked the teacher to revise their writing of recount text based on their experience as their exercise, and 4) The advantages of teaching structure using recount text were that the students became easier in mastering past tense. It was due to the fact that the teaching-learning process was based on the application of structure in text. The weakness of the teaching structure using recount text was time consuming since it needed more time to discuss the text, especially in translating each word into Indonesian that was caused by students' lack of vocabulary. Keywords: structure mastery, recount text understanding, classroom action research